ANALISIS MANAJEMEN MASJID DALAM MENGHADAPI ERA REVOLUSI INDUSTRI 4.0 - Mahmudi (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2022)
The Industrial Revolution 4.0 is not a barrier for mosques to develop their potential so that mosque functions can be carried out. This study focuses on the implementation of management, supporting and inhibiting factors, as well as the analysis of the Great Mosque of Daarul Muttaqien Balung, Jember Regency in facing the era of the industrial revolution 4.0. Identification of problems using descriptive qualitative methods with data collection techniques through interviews, observation, and documentation. The results obtained are the Great Mosque of Daarul Muttaqien Balung, Jember Regency, has implemented the functions of the mosque even though it has not been maximized. Based on the SWOT analysis, the Great Mosque of Daarul Muttaqien Balung, Jember Regency is in quadrant I which allows it to use a growth strategy. Meanwhile, the efforts made by mosques to adapt in the 4.0 era are still considered less than optimal due to limited facilities and experts